Personality type matters: Perceptions of job demands, job resources, and their associations with work engagement and mental health - Herr, Raphael; Van Vianen, Annelies E. M.; Bosle, Catherin; Fischer, Joachim E. (Current psychology, 2023)
This three-wave study examined whether the pattern of associations of job demands and job resources with work engagement and mental health depends on personality types. In a representative sample of the German workforce (N = 13,665), the Big Five personality traits could be used to cluster participants into five personality types: ordinary, resilient, strained, overcontrolled, and undercontrolled. As predicted, job demands were associated with mental health and job resources were primarily associated with work engagement. However, these relationships differed across personality types. We conclude that research and practice could take a more personality-driven stance towards employee perceptions of job demands and job resources and their associations with work engagement and mental health.
Online veröffentlicht: 14. April 2021
Gesehen am 05.07.2023